Recurrence of Recent Breast Abscesses — A Clinical Analysis (The Planet, 2024)
Introduction: A common occurrence among nursing women, breast infections are typically caused by ascending infections. The purpose of this research is to investigate the root cause of female breast infections. Prompt and effective care of breast infections is crucial because of the delicate nature of the functioning breast tissue. The aim of the study is to assess recurrence of recent breast abscesses. Materials & Methods: This cross-sectional observational study was conducted at Department of Surgery, Dhaka Medical College Hospital, Dhaka from August 2014 to February 2015. Sixty (60) cases from patients who attended inpatient and outpatient departments with breast pathology were selected according to inclusion and exclusion criteria. All data encompassing variables, clinical presentation, diagnosis, type of treatment, preoperative and postoperative investigation findings and outcome of treatment were noted and recorded in a structured questionnaire. Results: Age of the patients ranged from 16 years to 55 years. Underlying clinical conditions were found in 12 (20%) patients namely diabetes (6.67%), tuberculosis (3.33%), granulomatous mastitis (3.33%), antibioma (3.33%), inadequate drainage of previous abscess (3.33%). Pattern of recent breast abscess found compatible with abscess was (non-specific) (90%), tubercular (3.33%), granulomatous mastitis (3.33%), and antibioma (3.33%). We found postoperative recurrence in 6(10%) of patients due to inadequate drainage 2(3.33%), tuberculosis 2(3.33%) and granulomatous mastitis 2(3.33%). Conclusion: Although rare, underlying clinical conditions associated with breast infections in women are recognised clinical entities that require specific attention. Every time possible, a clinical problem should be looked for and treated.
Keywords: Breas tabscess; Pathological trend; Granulomatous mastitis